STATE ADMINISTRATION OF SOCIO-ECONOMIC STABILITY OF THE COUNTRY AND THE APPLICATION PECULIARITIES OF THE ANTI-CRISIS MEASURES IN WARTIME CONDITIONS - Savkiv , U. S.; Leshchuk , H. V.; Sydor , H. V. (The actual problems of regional economy development, 2024)
The article is aimed at studying the socio-economic stability of the state in modern economic conditions. It has been determined that the war in Ukraine had prompted a revision of approaches to the formation of socio-economic policy, state regulation, and the search for effective management methods. The main task of managers at all levels of the government is to develop the appropriate strategic plans and ensure their effective implementation. Practically all links of the national economic system suffered significant losses: production decreased, ports were blocked, there were negative trends in foreign trade, there was a loss of social capital of our country, as well as a high level of migration and unemployment, which is a great threat to the socio-economic system of our country. The main forecast macroeconomic indicators of economic and social development of Ukraine for 2024–2026 have been studied and the priorities of the economic development during and after the war have been defined; the anti-crisis measures of state policy and management decisions are proposed to overcome the crisis caused by the war in Ukraine. The purpose of the article is to identify the problems of ensuring the socio-economic stability of the state and determine the priorities and targets of the social and economic development of the country during and after the war. To achieve this goal, the article uses such research methods as the system analysis to study the factors that provoke socio-economic instability in the state; the synthesis and the integrated approach to form anti-crisis measures of state policy and management decisions to overcome the crisis caused by the war in Ukraine; the abstraction for the formation of generalized conclusions. The scientific novelty of the research is to determine the priority directions of economic development of the country during the war and the formation of anti-crisis measures of state policy to overcome the crisis caused by the war. The results of scientific research can be applied in the system of public administration to stabilize the social and economic development of the state in war.